A Study on Biological Spoilage of Fruits and Vegetables under Refrigeration: Understanding the Causes and Effects of Biological Spoilage in Refrigerated Fruits and Vegetables (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Food spoilage can be described as a change of sensory (tactile, visual, olfactory, or flavor) which is considered undesirable by the user. Food chain spoilage may occur at any point. Insect injury, physical harm, indigenous enzyme activity in animal or plant tissue or microbial infections can trigger spoilage. Many natural foods are life-limited. Perishable items like seafood, fruit, and bread are short-lived. Some things may be stored longer but ultimately decomposes. Enzymes can induce polymer degradation of certain foods whereas chemical reactions such as oxidation and rancidity decompose others, but the key common cause of food spoilage is microorganism invasion such as molds, yeast and bacteria. In case of mold spoilage, fluffy development covers the meal, being sticky and sometimes smelling unpleasant. Bacterial infection is more harmful since, while seriously contaminated, food sometimes doesn't look awful, it growing seem very natural. The presence of potentially harmful contaminants and bacterial spores is also not observed until after an epidemic of food poisoning.